From Blue to Gray: Inflammation and Neurodegeneration in Depression - Ebrahim Haroon (Journal of Affective Disorders Reports, 2023)
Depressed patients experience a 2-5-fold increased risk of neurodegenerative disorders, including Alzheimer's dementia. Understanding mechanisms underlying neurodegenerative risk will help control progressive neuropathology and prevent dementia in MDD. Our previous data have associated chronic inflammatory activation in depression with increases in neurotoxic molecules such as kynurenines and glutamate, further linked to cognitive dysfunction. Recent developments in bioassay technology have enabled reliable detection of immune and neurodegeneration markers such as neurofilament light chain (NFL), glial fibrillary acidic protein (GFAP), Tau, and amyloid beta (abeta) in the cerebrospinal fluid (CSF). Herein, we hypothesized that increases in CSF inflammatory markers would be associated with increases in makers of neurodegeneration in the CSF and diffusion tensor imaging (DTI) in depressed (with and without cognitive dysfunction) versus controls. Fifty-four subjects (35 depressed and 19 non-depressed control subjects) participated in the study provided CSF samples and clinical and demographic information. Mean diffusivity (MD), fractional anisotropy (FA), and Neurite Orientation Dispersion Density Imaging (NODDI)-based diffusion measures were estimated in 42 predefined white matter bundles within each subject. Of the inflammatory markers, CSF TNFR2 was differentially associated with CSF NFL and GFAP as a function of depressed group status(p-corr<0.001). CSF TNFR2/NFL (pcorr=0.02) and TNFR2/GFAP (pcorr=0.006) association was significant in the depressed subjects with cognitive dysfunction compared to depressed subjects without cognitive dysfunction and control subjects. CSF NFL and GFAP were associated with decreased fractional anisotropy of the right frontal aslant tract (p-corr=0.02 and 0.03, respectively) and increased mean diffusivity of right anterior thalamic radiation (p-corr=0.047 and 0.008, respectively) only among depressed subjects. In addition, CSF NFL was associated with an increased orientation dispersion index (p-corr=0.04) in the left arcuate fasciculus among depressed groups. No associations were noted among control subjects. Depressed subjects with increases in inflammation may represent a high-vulnerability group at risk for the development of dementia.